The Mechanism Action of German Chamomile (Matricaria recutita L.) in the Treatment of Eczema: Based on Dose–Effect Weight Coefficient Network Pharmacology - Wang, Wenfei; Wang, Yichun; Zou, Junbo; Jia, Yanzhuo; Wang, Yao; Li, Jia; Wang, Changli; Sun, Jing; Guo, Dongyan; Wang, Fang; Wu, Zhenfeng; Yang, Ming; et al. (Frontiers in Pharmacology, 2021)
To determine the active ingredients in German chamomile volatile oil and the mechanism of action in the treatment of eczema, this study used two parameters (ingredient content and oil–water partition coefficient) and established a new network pharmacology method based on the dose–effect weight coefficient. Through the new network pharmacology method, we found that German chamomile volatile oil regulated T-cell lymphatic subpopulations to inhibit the Th17 cell differentiation signaling pathway. This resulted in a reduction of interleukin 17 (IL-17), thereby inhibiting the activation of the nuclear factor kappa beta (NF-κB) and MAPK pathways, decreasing the secretion of the pro-inflammatory factors (tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6)), and reducing inflammation. In this study, a new dose–effect relationship synergistic network pharmacology method was established to provide a new method for the screening of effective ingredients and pathways of drugs, and to provide a basis for the follow-up studies of German chamomile volatile oil in the treatment of eczema.